Etnisitas dalam Otonomi Daerah - Gustiana Anwar Kambo (The Politics : Jurnal Magister Ilmu Politik Universitas Hasanuddin, 2015)
Abstract : This paper aims to describe ethnocentrism issues as the consequences of Law on Regional Autonomy. Starting from the article that became the foundation of Regional Autonomy Law, including the issuing of Law number 22 of 1999, then the review of ethnocentrism phemomena due to implementation of Regional Autonomy Law. In addition, this paper also discusses the formation of the West Sulawesi Province as one form of ethnicity implementation.Keywords: Ethnicity, Regional Autonomy, Law